2018
DOI: 10.1001/jama.2018.7480
|View full text |Cite
|
Sign up to set email alerts
|

Scabies

Abstract: Scabies is a contagious skin infestation caused by tiny mites.The microscopic, 8-legged human itch mite digs into the skin to feed and lay eggs; however, it cannot survive outside human skin for more than 2 to 3 days. Scabies is transmitted by direct person-to-person contact or through objects that carry the mites, such as clothing and bedding. Scabies can affect anyone but is most common in children and crowded populations, such as jails, refugee camps, and nursing homes. Because scabies is a human parasite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…The incubation period is reported as approximately 2‐3 weeks in scabies. Sarcoptes that can live outside the body for 3 days at average room temperature may remain contagious for up to 10 days in hyperkeratotic shells 12,13 . In a study conducted by Cengiz et al in our country, it has been reported as one of the most crucial admission causes of scabies disease 11 .…”
Section: Discussionmentioning
confidence: 94%
“…The incubation period is reported as approximately 2‐3 weeks in scabies. Sarcoptes that can live outside the body for 3 days at average room temperature may remain contagious for up to 10 days in hyperkeratotic shells 12,13 . In a study conducted by Cengiz et al in our country, it has been reported as one of the most crucial admission causes of scabies disease 11 .…”
Section: Discussionmentioning
confidence: 94%
“…Sarcoptes, which can live for 3 days outside the body at normal room temperature, can remain infectious for up to 10 days in hyperkeratotic crusts and become very infectious. 5,6 In this regard, there are several explanations that can be addressed increasing number of scabies-related patients during the pandemic. Firstly, the temporary workplace closure in the urban areas which are sources of the COVID-19 outbreak allowed patients to migrate from urban to rural areas where scabies can be seen as more commonly.…”
mentioning
confidence: 99%
“…hominis, is a common, highly contagious skin disease which spreads through direct skin contact. 1 Classical scabies is not readily transmitted via fomites but patients with crusted scabies who harbour millions of mites may transmit them through their apparels. 1,2 Outside the human body the mites can survive for 24 to 36 hours at normal room temperature of 21°C and 40 to 80% relative humidity.…”
Section: Shital Poojary Saurabh Jaiswal Akshat Wahi 1 Aparajita Sahoo 1 Forum Shah 1 Geetanjali Rathod 1 Anshuman J Dasmentioning
confidence: 99%
“…1 Classical scabies is not readily transmitted via fomites but patients with crusted scabies who harbour millions of mites may transmit them through their apparels. 1,2 Outside the human body the mites can survive for 24 to 36 hours at normal room temperature of 21°C and 40 to 80% relative humidity. 3 This experimental study, conducted at Siriraj Hospital, Thailand, aimed to identify the optimal heat and exposure time needed to destroy scabies mites and their eggs.…”
Section: Shital Poojary Saurabh Jaiswal Akshat Wahi 1 Aparajita Sahoo 1 Forum Shah 1 Geetanjali Rathod 1 Anshuman J Dasmentioning
confidence: 99%